An Urban Middle-Class Calling: Women and the Emergence of Modern Nursing Education at the Toronto General Hospital, 1881-1914 - Jardine, Pauline (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1989)
This paper examines the prime factors in the emergence of modern nursing from 1881 to 1914 at Toronto General Hospital School for Nurses (TGH). Based on primary sources in the TGH archives and early issues of The Canadian Nurse, the paper reveals that ethical principles, academic achievement, and a new public image derived from the middle-class thrust in nursing education were the basic components that led to the evolution of the trained nurse. It further explores the extent to which the nursing profession in a major teaching hospital was influenced by educated middle-class women.